Peripheral nerve involvement in Friedreich's ataxia characterized by quantitative magnetic resonance neurography - Jacobi, Heike; Weiler, Markus; Sam, Georges; Heiland, Sabine; Hayes, John M.; Bendszus, Martin; Wick, Wolfgang; Hayes, Jennifer (European journal of neurology, 2025)
BACKGROUND: Friedreich's ataxia (FRDA) affects both the central and peripheral nervous system. Peripheral nerve involvement manifests predominantly as a progressive sensory neuropathy caused by dorsal root ganglionopathy. An additional direct involvement of peripheral nerves leading to abnormal myelination is increasingly discussed. Here, we characterize lower extremity peripheral nerve involvement in FRDA by quantitative magnetic resonance neurography (MRN). - METHODS: Sixteen genetically confirmed FRDA patients and 16 age-/sex-matched controls were prospectively enrolled. Patients underwent neurologic examinations and nerve conduction studies (NCS). Large-coverage MRN of sciatic and tibial nerves was conducted utilizing dual-echo turbo-spin-echo sequences with spectral fat saturation for T2-relaxometry, and two gradient-echo sequences with and without off-resonance saturation rapid frequency pulses for magnetization transfer contrast imaging. Microstructural and morphometric MRN markers including T2-relaxation time (T2app), proton spin density (ρ), magnetization transfer ratio (MTR), and cross-sectional area (CSA) were calculated to characterize nerve lesions. - RESULTS: Tibial nerve ρ and T2app were markedly decreased in FRDA at the thigh (ρ: 368.4 ± 11.0 a.u.; T2app: 59.5 ± 1.8 ms) and lower leg (ρ: 337.3 ± 12.6 a.u.; T2app: 53.9 ± 1.4 ms) versus controls (thigh, ρ: 458.9 ± 9.5 a.u., p < 0.0001; T2app: 66.3 ± 0.8 ms, p = 0.0019; lower leg, ρ: 449.9 ± 12.1 a.u., p < 0.0001; T2app: 62.4 ± 1.2 ms, p < 0.0001) and correlated well with clinical scores, disease duration, and NCS. MTR and CSA did not differentiate between FRDA and controls. - CONCLUSION: Our study results provide a profound characterization of peripheral nerve involvement in FRDA. The identified good correlation between ρ and T2app with clinical symptom scores and NCS suggests that parameters of T2 relaxometry may become relevant biomarkers to monitor disease progression and therapeutic responses in potential future clinical trials.
Gesehen am 05.11.2025